2020
DOI: 10.1088/1748-0221/15/04/p04010
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface detection of opaque and solid material defect based on photoacoustic effect

Abstract: This study develops a subsurface detection system based on a photoacoustic effect. The main parts of the system are a laser diode as an exciter, a standard microphone as an acoustic detector, and a software-based phase sensitive detection (PSD) method. Artificial defects of various depths were made inside an alumunium plate as the object which was painted with acrylic paint to cover the defects. The difference in the thermal diffusivity of alumunium and acrylic paint will cause different amplitudes of photoaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Weak signal measurement methods are developed in many fields, such as the use of inverse weak value amplification, 81 the I/V conversion measurement method, 82 coupled-resonator systems, 83 and lock-in amplifiers. 84 Wibowo, et al suggested using an OA circuit with LM 358 as a basic differential amplifier to overcome the small output voltage of the MR chip. 40,85 OA ICs offer output voltage amplification circuit design freedom due to their high voltage gain (up to 100 dB).…”
Section: Working Principle Of Boc Based On the Tmr/ionps Coupled Sensorsmentioning
confidence: 99%
“…Weak signal measurement methods are developed in many fields, such as the use of inverse weak value amplification, 81 the I/V conversion measurement method, 82 coupled-resonator systems, 83 and lock-in amplifiers. 84 Wibowo, et al suggested using an OA circuit with LM 358 as a basic differential amplifier to overcome the small output voltage of the MR chip. 40,85 OA ICs offer output voltage amplification circuit design freedom due to their high voltage gain (up to 100 dB).…”
Section: Working Principle Of Boc Based On the Tmr/ionps Coupled Sensorsmentioning
confidence: 99%
“…Composite materials are often used as major components of supporting structure owing to their high strength, high modulus, and good fatigue resistance, and they are widely applied in automotive manufacturing [1][2][3], aerospace [4][5][6], infrastructure [7][8][9][10] and other various fields. However, due to the complexity and instability of the manufacturing process of composite materials, as well as the influence of the environment during the service life, various types of defects may arise, such as delamination, porosity, and fiber wrinkles and so on [11][12][13][14][15]. These defects will affect the mechanical performance of the components involved, and may lead to serious safety accidents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in recent studies based on modulated laser exposures to material and as a result analyzing stress waves [2]. Photoacoustic effect, besides optical absorption, thermal expansion and material due to its mechanical properties, has been the subject of many studies on the determination of material properties or defects [3]. Some of well-known applications are the detection of gas-type and small-scale materials or materials solved in liquids [4].…”
Section: Introductionmentioning
confidence: 99%